2015
DOI: 10.1017/s1366728915000164
|View full text |Cite
|
Sign up to set email alerts
|

The development of shared syntax in second language learning

Abstract: According to Hartsuiker et al.'s (2004) shared-syntax account bilinguals share syntactic representations across languages whenever these representations are similar enough. But how does such a system develop in the course of second language (L2) learning? We will review recent work on cross-linguistic structural priming, which considered priming in early second language learners and late second language learners as a function of proficiency. We will then sketch our account of L2 syntactic acquisition. We assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
223
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(272 citation statements)
references
References 61 publications
39
223
10
Order By: Relevance
“…Indirect Object). Interpreting our results within the developmental model of L2 syntactic acquisition (Hartsuiker and Bernolet 2017), this structural overlap had a more facilitating effect for higher-proficiency participants because they are equipped with more abstract representations of Irish (L2) structures, presumably allowing for a greater degree of connectedness with existing representations of English (L1) structures.…”
Section: Mixed Logit Model Of Dative Responsessupporting
confidence: 54%
See 3 more Smart Citations
“…Indirect Object). Interpreting our results within the developmental model of L2 syntactic acquisition (Hartsuiker and Bernolet 2017), this structural overlap had a more facilitating effect for higher-proficiency participants because they are equipped with more abstract representations of Irish (L2) structures, presumably allowing for a greater degree of connectedness with existing representations of English (L1) structures.…”
Section: Mixed Logit Model Of Dative Responsessupporting
confidence: 54%
“…The developmental account of L2 syntactic acquisition (Hartsuiker and Bernolet 2017) has implications for the relative strength of between-versus withinlanguage priming effects, since it predicts that only highly proficient bilinguals with fully integrated structural representations should prime as strongly between languages as within. Several studies have found evidence for equivalent effects, independent of the priming language (e.g., Schoonbaert et al 2007;Kantola and Van Gompel 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, prior research on priming in L2 production revealed that L2 syntactic representation develops with participants' language learning experience and proficiency, with lower-proficiency participants relying more on lexically specific syntactic representations (see Hartsuiker and Bernolet, 2015, for a review). To explore whether syntactic representations involved in L2 comprehension are also modulated by proficiency, we recruited participants of different L2 education levels (and proficiency), to be detailed in the following section.…”
Section: Introductionmentioning
confidence: 99%